Product evaluation on the Chinese language program for international students in a Chinese university - Xianjun, Tan; Pang, Vincent Ah Fook (Science Research Society, 2021)
HanyuShuipingKaoshi (HSK) is an international standardized test, which means Chinese Proficiency Test in English. A minimum of HSK level 4 is needed for an international student to apply for an academic programme taught in Chinese language in the universities of China. Guided by product evaluation of Context, Input, Process, Product (CIPP) model, the test scores of HSK level 4 of the international students in a Chinese university are analyzed using effect size. Feedbacks from the international students who failed in the test of HSK level 4 are collected based on a questionnaire formulated by the researchers. The strengths, weaknesses, causes of failure and improving direction of the one academic year’s Chinese language program in this Chinese university are identified through the evaluation. The research aims to provide references for the improvement of Chinese language teaching in this Chinese university and universities with the same context. The research enriches the literature concerning the evaluation on Chinese language teaching and learning for international students in China.